2000
DOI: 10.2174/1381612003400371
|View full text |Cite
|
Sign up to set email alerts
|

Seocalcitol (EB 1089) A Vitamin D Analogue of Anti-cancer Potential. Background, Design, Synthesis, Pre-clinical and Clinical Evaluation

Abstract: It is well established that the metabolically active form of vitamin D, 1alpha,25-dihydroxyvitamin D3 (1alpha,25(OH)2D3) plays a key role in the establishment and maintenance of the calcium metabolism in the body. In addition to this classic effect of 1alpha,25(OH)2D3, substantial evidence has emerged demonstrating that 1alpha,25(OH)2D3 is able to regulate cell growth and differentiation in a number of different cell types, including cancer cells. However, the clinical usefulness of 1alpha,25(OH)2D3 is limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
75
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(79 citation statements)
references
References 123 publications
2
75
0
2
Order By: Relevance
“…Clinical studies using EB1089 as treatment of different cancer types have demonstrated that the drug has no severe hypocalcaemia effects in humans (Gulliford et al, 1998;El Abdaimi et al, 1999). It has recently been reported that the development of Seocalcitol TM is active as an anti-cancer drug (Hansen et al, 2000). We therefore suggest that Seocalcitol™ (EB1089) may prove useful in treatment of breast cancer patients who have relapsed on antioestrogen treatment, and that the Bcl-2 expression level may be used to select the patients most likely to respond to treatment with Seocalcitol TM .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Clinical studies using EB1089 as treatment of different cancer types have demonstrated that the drug has no severe hypocalcaemia effects in humans (Gulliford et al, 1998;El Abdaimi et al, 1999). It has recently been reported that the development of Seocalcitol TM is active as an anti-cancer drug (Hansen et al, 2000). We therefore suggest that Seocalcitol™ (EB1089) may prove useful in treatment of breast cancer patients who have relapsed on antioestrogen treatment, and that the Bcl-2 expression level may be used to select the patients most likely to respond to treatment with Seocalcitol TM .…”
Section: Discussionmentioning
confidence: 98%
“…It is therefore of extreme importance to obtain a detailed knowledge of anti-oestrogen resistance to further improve treatment of patients relapsing on anti-oestrogen treatment. The vitamin D analogue EB1089 is an interesting new and promising anti-cancer drug detailed reviewed in Hansen et al (2000). It has been shown to be highly antiproliferative and to induce apoptosis in breast cancer cells both in vitro and in vivo without causing hypocalcaemia (Mathiasen et al, 1993;Love et al, 1996;Xie et al, 1997Xie et al, , 1999Gulliford et al, 1998;James et al, 1998;El Abdaimi et al, 1999;Mathiasen et al, 1999).…”
mentioning
confidence: 99%
“…Despite the efforts of industry to develop less calcaemic 1,25D surrogates, e.g., Seocalcitol (EB1089, [61], these molecules still exhibit a toxic hypercalcaemic action during the treatment, for example, of inoperable pancreatic carcinoma [62]. Since 24R,25D would not appear to share the pro-catabolic actions of 1,25D we are exploring the potential of this molecule to stimulate bone matrix accrual in association, for example, with bone graft substitutes as used for revision arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…More than 50 genes have been shown to be regulated by this mechanism, among these the cell cycle regulators p21, p27, c-fos and c-myc. Regulation of these genes may in turn explain the antiproliferative and differentiating effects of vitamin D and analogues (for a review see (Hansen et al (2000)), as well as their ability to inhibit the invasive potential of human cancer cells in vitro (Hansen et al, 1994) and to inhibit tumour-induced angiogenesis (Majewski et al, 1993).…”
mentioning
confidence: 99%
“…In search of a compound with less effect on calcium metabolism a new vitamin D analogue, Seocalcitol, has been synthesised (Hansen et al, 2000). Seocalcitol is 50 -200 times more potent in inhibiting proliferation and inducing differentiation of human cancer cell lines than 1a,25-dihydroxyvitamin D 3 (Hansen and Mäenpää, 1997).…”
mentioning
confidence: 99%